Application of project-based learning (pbl) to motivate english learning of ninth year students of Unidad Educativa Particular Eloy Alfaro of Machala city, during the first term of 2012-2013 academic year - Apolo Chávez, Anyela (2013)
The present research project was developed following the scheme established by the Army Polytechnic School Language Department. It details and specifies the procedure needed to reach the objectives of the research and obtain the results which allow to formulate a proposal that will be able to find a way to solve the founded problem. This research is focused on the application of Project-Based Learning (PBL) to motivate English Learning of Ninth year students of Unidad Educativa Particular Eloy Alfaro from Machala City, during the first term of 2012- 2013 academic year¿. Dependent and Independent variables have been determined and categorized in the theoretical frame in order to obtain the main items to formulate inquiry tools as interview, surveys and a questionnaire, which will allow to obtain the required data to set up a proposal. Analysis and interpretation of the outcomes will be used to set up the study conclusions and recommendations directly related to the general and specific objectives established at the beginning of the investigation. This research is based on the application of methodological project-based learning (PBL) in order to increase the interest and motivation of English learning and at same time through his methodological strategy, it allows teachers to develop effectively skills, critical thinking and meaningful learning of their students.